Respostas

A melhor resposta!
2014-08-05T19:34:42-03:00
Vamos utilizar basicamente três propriedades de potência..
a^n*a^m=a^{n+m}
a^n/a^m=a^{n-m}
(a^n)^m=a^{n*m}

Item a


2,5*10^7*4*10^{-3} 

2,5*4*10^7*10^{-3}

10*10^7*10^{-3}=10^{1+7-3}=\boxed{10^{5}}

Item b

1,25*10^{-8}*8*10^6

1,25*8*10^{-8}*10*^6

10*10^{-8}*10^6=10^{1+(-8)+6}=\boxed{10^{-1}}

Item c

 \frac{6*10^8}{1,2*10^7}=5*10^{8-7}=5*10^1=\boxed{50}

Item d

0,0008*15000000

8*10^{-4}*1,5*10^{7}

1,5*8*10^{-4}*10^7

12*10^{-4}*10^{7}=12*10^{-4+7}=12*10^3=\boxed{1,2*10^4}

Item e

(3*10^2)^3=3*10^{2*3}=\boxed{3*10^6}

Item f

2^4*10^{-5}*2^{-2}*10

2^4*2^{-2}*10^{-5}*10=2^{4+(-2)}*10^{-5+1}=2^2*10^{-4}=\boxed{4*10^{-4}}

Item g

(0,002)^2*500^2

(2*10^{-3})^2*500^2=4*10^{-6}*250000=250000*4*10^{-6}

1000000*10^{-6}=10^6*10^{-6}=10^{6+(-6)=\boxed{10^0}

Item h

 0,027*3000/0,09

27*10^{-3}*3*10^3/(9*10^{-2})^2

81*10^0/81*10^{-4}

10^4


3 5 3